The cute and the cool : wondrous innocence and modern American children's culture - Cross, Gary S. (Oxford University Press, 2010)
The cute child — spunky, yet dependent, naughty but nice — is largely a 20th-century invention. This book examines how that look emerged in American popular culture and holidays and how the cute turned into the cool, seemingly its opposite, in stories and games. It shows how adults have created the ideal of the innocent childhood and have used this to project adult needs and frustrations rather than concerns about protecting and nurturing the young — and how the images, goods, and rituals of childhood have been co-opted by the commercial world. Magazine and TV advertisements, articles from the popular press, comic strips, movies, radio scripts, child-rearing manuals, and government publications support this argument and the book is illustrated with cartoons, toys, ads, and photos.
Keywords: Innocence (Psychology); Parenting : History : United States; Toys : Social aspects : United States; Children in popular culture; Children : History : United States; Children : Caricatures and cartoons : United States; sosiologia; historia; lastenkulttuuri; populaarikulttuuri; lapsuus; lapset (ikäryhmät); leikkikalut; vanhemmuus; Yhdysvallat